2015
DOI: 10.1021/cs501673g
|View full text |Cite
|
Sign up to set email alerts
|

A Consistent Reaction Scheme for the Selective Catalytic Reduction of Nitrogen Oxides with Ammonia

Abstract: For the first time, the standard and fast selective catalytic reduction (SCR) of NO by NH3 are described in a complete catalytic cycle that is able to produce the correct stoichiometry while allowing adsorption and desorption of stable molecules only. The standard SCR reaction is a coupling of the activation of NO by O2 with the fast SCR reaction, enabled by the release of NO2. According to the scheme, the SCR reaction can be divided into an oxidation of the catalyst by NO + O2 and a reduction by NO + NH3; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

54
582
9
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 436 publications
(646 citation statements)
references
References 89 publications
54
582
9
1
Order By: Relevance
“…Recent operando XAS studies by Lomachenko et al [15] demonstrate that, above 300 • C, mobile Cu components quickly diminish and four coordinated Cu(II) complexes convert to 3 coordinated ones that spectroscopically resemble a [Cu(II)-NO 3 − ]-Z species. This finding may be used to justify an SCR mechanism proposed by Janssens et al [13], who postulated that Cu(I) oxidation to Cu(II) is achieved by nitrate intermediate formation from NO+O 2 as the rate-limiting step:…”
Section: Standard Nh 3 -Scrmentioning
confidence: 63%
See 3 more Smart Citations
“…Recent operando XAS studies by Lomachenko et al [15] demonstrate that, above 300 • C, mobile Cu components quickly diminish and four coordinated Cu(II) complexes convert to 3 coordinated ones that spectroscopically resemble a [Cu(II)-NO 3 − ]-Z species. This finding may be used to justify an SCR mechanism proposed by Janssens et al [13], who postulated that Cu(I) oxidation to Cu(II) is achieved by nitrate intermediate formation from NO+O 2 as the rate-limiting step:…”
Section: Standard Nh 3 -Scrmentioning
confidence: 63%
“…Thus, it is necessary to generate intermediates with an N oxidation state of +3 for a viable mechanism. In the proposal by Janssens et al [13], this is achieved by the following reaction:…”
Section: Standard Nh 3 -Scrmentioning
confidence: 99%
See 2 more Smart Citations
“…The total emission of NOx ultimately depends on the oxidation of fuel-N and the reduction of NO. [5][6][7][8] The research of NOx's generation and discharge in sintering process has drawn much attention in recent years. Studies have shown that sintering parameters such as water ratio, fuel ratio, quicklime ratio and the thickness of bed layer had important influences on the NOx concentration in flue gas.…”
Section: Introductionmentioning
confidence: 99%